Effect of Tetrodotoxin from Crude Puffer Fish (Tetraodon fluviatilis) Liver Extract on Intracellular Calcium Level and Apoptosis of HeLa Cell Culture - Natanael Untario; Titik Cinthia Dewi; M. Aris Widodo; Pudji Rahaju (Journal of Tropical Life Science, 2017)
Cervical cancer is the third most commonly diagnosed cancer and fourth leading cause of women death with 8% of total death caused by cancer in women in 2008. Tetrodotoxin (TTX) is a potent neurotoxin found in inner organs puffer fish, with the specific mechanism of sodium channel blocking, and widely used for research purposes. Previous reports claimed that TTX has the capability of inhibiting the metastatic process of cancer and apoptotic effect. Studies also show that apoptosis is a process involving the increase of intracellular calcium level, yet the connection between TTX and increase of intracellular calcium level, therefore triggering apoptosis, has not been established. This is an experimental study with post test only control group design, carried out by exposing HeLa cell culture to a crude liver extract of a puffer fish species, Tetraodon fluviatilis. Crude puffer fish liver extract is administered into HeLa cell culture well in different concentrations 10-4, 10-2, and 10-1. Intracellular calcium level and apoptosis were then measured after 18 hours of incubation. Measurements of intracellular calcium level were done by using CLSM with Fura-2AM staining, and apoptosis by using flowcytometry with Annexin V/PI. Â The result shows that there is a significant difference between samples both in intracellular calcium (p < 0.05) and apoptosis (p < 0,05). Both intracellular calcium and apoptosis levels are proportional to liver fish extract concentration. Pearsonâ€™s correlation test shows correlation between treatment and intracellular calcium levels (p = 0.000), between treatment and apoptosis (p = 0.002), but not between intracellular calcium and apoptosis (p = 0.05). These results suggest that TTX induces an increase in intracellular calcium level and apoptosis, but calcium pathway is not the sole cause of the apoptosis.Â